Questioning the relevance of supplier satisfaction for preferred customer treatment: Antecedent effects of comparative alternatives and multi-dimensionality. Issue 1 (January 2021) - Piechota, Steffen; Glas, Andreas H.; Essig, Michael
Abstract: Through the construct of supplier satisfaction, recent research explains the supplier's preferred treatment of a given customer. This cause-and-effect phenomenon is often not contrasted with other reasons or controlled for. This work addresses this issue and uses two tactics to elaborate upon social exchange theory, namely, construct splitting and construct contrasting, to analyse the development of preferential customer treatment. For this purpose, a structural equation model is used with data from the international automotive industry. The results extend the breadth of constructs explaining preferred customer treatment (PCT) and challenge the existing reasoning by questioning the relative importance of supplier satisfaction. While supplier satisfaction does affect PCT, the relative supplier satisfaction defined as a comparison of outcomes between the actual and the best alternative business relationships influences PCT much more. Furthermore, by distinguishing between the economic and non-economic dimensions of supplier satisfaction, the study indicate that economic satisfaction has a higher influence on the relative satisfaction whereas social satisfaction a higher one on absolute supplier satisfaction. These findings imply that despite the current debate about the importance of behavioural constructs such as supplier interaction and social capital, supplier resource allocation decisions are actually dominated by economic and relative aspects of satisfaction. This outcome calls for a more economically driven debate about behavioural supply management approaches. Highlights: Influence of supplier satisfaction on resource allocation tested via supplier survey. Satisfaction proved to be sufficient condition for preferred customer status. Relative evaluation of relationship outcomes was identified as necessary condition. Relative outcome evaluation was predominantly influenced by economic satisfaction. Social satisfaction showed a stronger effect on overall satisfaction than economic.